Targeted therapy acts to sensitize stereotactic body radiotherapy for pulmonary oligometastases from colorectal cancer - Sun, Xiye; Shu, Pei; Shen, Yali; Li, Zhiping; Liu, Ning; Ouyang, Ganlu; Tang, Yuanling; Huang, Meijuan; Wang, Xin (Frontiers in Oncology, 2025)
BackgroundStereotactic body radiation therapy (SBRT) is used to manage lung metastases arising from colorectal cancer (CRC), but its effectiveness is constrained by the radioresistance of CRCs. Here, we explored whether concurrent therapy with cetuximab or bevacizumab could improve the prognosis of CRC patients with pulmonary oligometastases.Materials and methodsCRC patients with oligometastatic lung tumors (OLTs) treated with concurrent chemoradiotherapy from March 2011 to March 2023 were retrospectively analyzed. Treatment outcomes for local control rate (LCR), progression-free survival (PFS), overall survival (OS), and toxicities were assessed.ResultsSixty-nine patients were included, with a median follow-up of 34 months. The 1-year LCRs for SBRT + chemotherapy, SBRT + chemotherapy + bevacizumab, and SBRT + chemotherapy + cetuximab were 63.3%, 96.2%, and 94.4%, respectively. Incorporating bevacizumab or cetuximab significantly prolonged median OS compared to chemotherapy (61 vs. 46 vs. 24 months). Substantial differences in median PFS were noted, with durations of 5, 23, and 8 months for SBRT + chemotherapy, SBRT + chemotherapy + bevacizumab, and SBRT + chemotherapy + cetuximab, respectively. Our univariate analysis revealed that patients under targeted therapy of bevacizumab or cetuximab were linked to prolonged OS and PFS (p < 0.05). Tumor size <2 cm and median biologically effective dose (BED10) ≥100 Gy were correlated with higher local control rates (p < 0.05). Furthermore, comprehensive multivariate analysis confirmed that tumor sizes of <2 cm were linked to better local control (p < 0.05). All three combination regimens were well tolerated, and the occurrence of toxicities was higher in treatments involving targeted therapy.ConclusionCombining concurrent chemoradiotherapy with cetuximab or bevacizumab improves treatment outcomes, with manageable toxicity. Given the limited sample size of this study, larger studies such as prospective trials are needed.